Current Perspectives on Cardiomyopathies - Tsipis, Angelos (IntechOpen, 2018)
Advances in the understanding of cardiomyopathies and the growth of cardiology have paralleled one another. Over the years, many classification methods have been developed for cardiomyopathies based on aetiology, structural models and the functional approach. The new concepts and events that have occurred in cardiology generally and in cardiomyopathies specifically are sufficient changes to justify this book. Developments in cardiomyopathies have advanced at a rapid rate, largely because of the progress that has been made in instrumental analysis and the integration of clinical cardiology with other fields of basic research. The material in this book encompasses and blends the knowledge recently acquired in genetics, pathology and physiology with the practical matters of diagnosis and treatment.